Enhancing the Nutritional Value of Coconut Meal for Aquaculture Feed through Fermentation with Rhizopus sp. and EM4 - Sigiro, Oktavia Nurmawaty; Tiwi, Tiwi; Asta, Hidayat; Marito, Shinta; Febrina, Asti; Hadipramudita , Bayu Seta; Yani, Fitri; Lidia, Lidia; Nurmiza, Nurmiza; Yuda, Yuda; Zakiah, Zakiah (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
Coconut meal is an agricultural waste that has not been widely utilized but still contains nutrients. This study aims to evaluate the effect of fermentation on the protein, fat, and carbohydrate content of coconut meal. Three main treatments were compared: unfermented coconut meal, coconut meal fermented with Rhizopus sp., and coconut meal fermented with EM4. The results of the analysis showed that unfermented coconut meal had a protein content of 34,77%, fat 8,84%, and carbohydrate 27,73%. Fermentation with Rhizopus sp. increased the protein content to 37,37%, decreased the fat content to 6.11%, and slightly increased the carbohydrate content to 23,04%. Meanwhile, fermentation with EM4 increased the protein content to 35.87%, decreased the fat content to 6.55%, and increased the carbohydrate content to 26.86%. Based on the results of the study, fermentation with Rhizopus sp. was more effective in increasing protein content and decreasing fat content compared to fermentation with EM4. Fermentation with EM4 showed a significant increase in carbohydrate content. In conclusion, the fermentation process can improve the nutritional quality of coconut meal, so that it can be a more nutritious alternative as animal feed